Penerapan Kaidah Bahasa Indonesia Sebagai Rujukan Penggunaan Bahasa Indonesia yang Baik dan Benar (Sintaksis dan Semantik) Serta Analisis Kesalahan Berbahasa Indonesia - Nur Aisyah Syarif; Rahma Ashari Hamzah; Nuru Zakina (Jurnal Bintang Pendidikan Indonesia, 2025)
Indonesian is very important in everyday life because it is the official language of the country and the main language for communication. Language errors still often occur, both orally and in writing. In this article, we will see how semantic and syntactic rules are used in Indonesian. It also covers some common mistakes that often occur, such as incorrect sentence structure, unclear meaning, and the use of words that are not in context. This article not only provides examples and analyzes errors, but also discusses the factors that cause these errors. Failure to understand sentence structure, the influence of regional languages, and the habit of using non-standard language on social media are examples of factors that cause these errors. The purpose of writing this article is to raise awareness of good and correct language, especially among students and prospective educators. With a better understanding of syntax and semantics, readers are expected to be more careful in constructing sentences and choosing the right words, so that communication becomes clearer and more effective. Good language shows talent and patriotism.